Fundamentals of ground engineering - Atkinson, John 1942- (CRC Press, 2014)
Fundamentals of Ground Engineering is an unconventional study guide that serves up the key principles, theories, definitions, and analyses of geotechnical engineering in bite-sized pieces. This book contains brief-one or two pages per topic-snippets of information covering the geotechnical engineering component of a typical undergraduate course in civil engineering as well as some topics for advanced courses. Written in note form, it summarizes the basic principles and theories of soil mechanics, the procedures for creating a geotechnical model, and the common analyses for slopes, foundations, and walls.